α-Sasakian 3-Metric as a Ricci Soliton - Kundu, S. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We prove that if the metric of a 3-dimensional α-Sasakian manifold is a Ricci soliton, then it is either of constant curvature or of constant scalar curvature. We also establish some properties of the potential vector field U of the Ricci soliton. Finally, we give an example of an α-Sasakian 3-metric as a nontrivial Ricci soliton.